Agro-ecological aspects of groundwater utilization: A case study - Shirazi, S.M.; Akib, Shatirah; Salman, Firas A.; Alengaram, Ubagaram Johnson; Jameel, Mohammed (Academic Journals, 2010)
Groundwater is an important source of irrigation and public supplies in Bangladesh. It is the main source of water available in Trishal upazila during dry season. The experimental soils were heterogeneous ranging from clay to silty clay loam. The results indicated that on an average soil pH, percentage nitrogen, organic carbon and sulphur were low and phosphorous was high in all land types. The lowest water level dropped below 8 m for 2 to 3 months in almost every year for all the location studied. The depths of water table in peak period of dry season (November to March) in Sutia River and in large, medium and small ponds were 0.95, 1.33, 0.45 and 0.00 m, respectively due to lowering of groundwater table. This situation eliminated the possibility of use of shallow tube wells (STWs) or other surface mounted suction mode pumps in Trishal upazila. Due to heavy abstraction of groundwater, many environmental consequences have been encountered during 20 years. Sowing time, pisciculture and growth of aquatic plants were seriously hampered. Likewise, oxygen deficiency in ponds, scarcity of water for domestic animal, and soil cracking in critical period occurred. Due to low humidity and relatively high temperature prevailing in the study area, the shallow rooted plants and vegetation which are not irrigated were drastically affected as evidence from field survey results. This might cause ecological imbalance in Trishal upazila.